Geostrateški pomen vodnih virov Slovenije - Plut, Dušan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2000)
The paper discusses basic geographical features and geostrategic interest of water resources in Slovenia. In comparison with other European countries Slovenia has abundant water resources which, however, are unevenly distributed and characteristic of seasonal watertable oscillations. In many cases, the economic and geostrategic interest of water resources is diminished by the poor water quality of streams. Slovenian rivers are not suitable for water supply, while the quality of groundwater and karst springs which are very sensitive in view of water-ecology are jeopardized in many cases by the untreated waste waters and other forms of environmental pollution. Waste waters' treatment and reasonable exploitation of water resources are also strategically important and sustainably devised tasks.
Keywords: onesnaževanje voda; oskrba z vodo; pitna voda; Slovenia; Slovenija; strateški pomen; varstvo voda; vodni viri